2015
DOI: 10.1371/journal.pone.0134309
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Use for Cervical Cancer Screening in Low-Resource Countries: A Pilot Study Conducted in Madagascar

Abstract: BackgroundVisual inspection of the cervix after application of 5% acetic acid (VIA) is a screening technique for cervical cancer used widely in low and middle-income countries (LMIC). To improve VIA screening performance, digital images after acid acetic application (D-VIA) are taken. The aim of this study was to evaluate the use of a smartphone for on- and off-site D-VIA diagnosis.Materials and MethodsWomen aged 30–65 years, living in the city of Ambanja, Madagascar, were recruited through a cervical cancer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 19 publications
1
76
0
Order By: Relevance
“…The TBDx system by applied visual sciences uses proprietary algorithms to detect and count acid fast bacilli at 40× magnification. Digital cytology systems have been extensively used in screening for cervical cancer ( 51 , 52 ). Combining these particular tests into a unified platform would provide a particularly attractive device in developing world settings where these diseases are highly prevalent and poorly diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…The TBDx system by applied visual sciences uses proprietary algorithms to detect and count acid fast bacilli at 40× magnification. Digital cytology systems have been extensively used in screening for cervical cancer ( 51 , 52 ). Combining these particular tests into a unified platform would provide a particularly attractive device in developing world settings where these diseases are highly prevalent and poorly diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature found that VIA sensitivity to detect CIN2þ in HPV-positive women was as low as 25% in Cameroon (37,38). The highest VIA sensitivity in HPVpositive women was 82% in a study from India (39), but this was considerably higher than the next highest sensitivity rate of 67% in Madagascar (36). We set VIA sensitivity in HPV-positive women at 70% to observe outcomes under a scenario of high performance.…”
Section: Discussionmentioning
confidence: 99%
“…The embedded mobile portal allows upload and real‐time data aggregation and monitoring and evaluation . In other applications, data exchange over mobile networks has been facilitated by cloud‐based data storage, multimedia messaging service or MMS, and electronic medical pathways . While mHealth technologies offer promising solutions for low‐resource settings, additional evidence on scalability and impact on health outcomes is needed …”
Section: Recent Advances and Promising Practicesmentioning
confidence: 99%
“…19,40,41 In Zambia, a system for telemedicine and quality assurance that combinesmobiletelecommunicationsanddigitalcervicographyplayed avitalroleinimprovingandscalingupvisualinspectionwithaceticacid (VIA)-based cervical cancer screening. 42,43 A similar approach using smartphonestocaptureandtransmitdigitalcervicalimageshasbeen successfullytestedinMadagascar, 44 andscaled-upinBotswana. 45,46 Takingmobiledigitalimagecaptureastepfurther,anenhancedvisual assessment (EVA) system tested in Kenya combines a smartphoneintegrated colposcope with a decision-support job aid that records dataonVIAtestresults,treatmentdecisions,andfollow-up/rescreen dates.Theembeddedmobileportalallowsuploadandreal-timedata aggregation and monitoring and evaluation.…”
Section: Smart Use Of Mobile and Other Technologiesmentioning
confidence: 99%
See 1 more Smart Citation